Solubility Enhancement of Cox-II Inhibitors by Cosolvency Approach - Babu, PR Sathesh; Subrahmanyam, CVS; Thimmasetty, J; Manavalan, R; Valliappan, K; Kedarnath, SA (Dhaka University Journal of Pharmaceutical Sciences, 2009)
Solubility enhancement of meloxicam and rofecoxib, which are poorly soluble in water, was attempted. These are available in the form of solid dosage forms but not in solution dosage forms due to their low aqueous solubility. In this work, aqueous solubility of meloxicam and rofecoxib was improved using the biocompatible solvents such as ethanol, propylene glycol, glycerin, and PEG 400. Physico-chemical properties of the solvents such as intermolecular interactions and the ability of the solvent to form a hydrogen bond with the drug molecules were found to be the major factors involved in the dissolution of drugs. It was found that less polar solvents were found to increase solubility by greater extent, thus accentuating hydrophobic interaction mechanism. Among the solvent blends studied, water-PEG 400 had highest solubilization potential. Thus, the study generated an important dataset so as to compare effect of various cosolvents on the solubility of the drugs. Key words: Aqueous solubility, Meloxicam, Rofecoxib, Cosolvency. doi: 10.3329/dujps.v7i2.2166 Â Â Â Dhaka Univ. J. Pharm. Sci. 7(2): 119-126, 2008 (December)